Subjects of democratic civilian control over the defense forces: interaction, features of legal regulation - Koropatnik, І.; Karelin, V.; Ostapenko, І. (Visnyk Taras Shevchenko National University of Kyiv Military-Special Sciences, 2022)
A scientific and legal study of the peculiarities of the legal regulation of the interaction of subjects in the system of democratic civilian control over the defense forces, as well as the current legislation and subordinate regulatory legal acts in the relevant field, was carried out. The concept of democratic civil control in the national legislation of Ukraine is studied. It was established that the presence of effective mechanisms of democratic civilian control is a guarantee of guaranteeing the constitutional foundations of a democratic, legal state in the field of national security and civilmilitary relations. Attention is focused on the fact that in the context of the general provisions of democratic civil control, without coordination and interaction it is not possible to ensure the mission of this activity. The category "interaction" was studied. Three main approaches to understanding the concept of interaction in legal science are distinguished, in particular: 1) functional; 2) communicative; 3) operational. Subjects in the system of democratic civilian control over the defense forces are singled out, which include: 1) President of Ukraine; 2) Supreme Rada of Ukraine; 3) National Security and Defense Council of Ukraine; 4) Cabinet of Ministers of Ukraine; 5) bodies of executive power; 6) local self-government bodies; 7) courts; 8) public institutions. The issue of the meaning of control functions is highlighted. The control activity of the President of Ukraine and the National Security and Defense Council of Ukraine is disclosed. The place of parliamentary control as a component of the mechanism of democratic civilian control over the defense forces is emphasized. The essence of the concept of public supervision as a type of civil control is revealed. Attention is focused on the need to ensure the interaction of subjects in the system of democratic civilian control over the defense forces. Emphasis is placed on the positive international experience of introducing the mechanism of democratic civil control.